Penguatan Peran Anggota Masyarakat Dalam Perencanaan, Penganggaran dan Penilaian Hasil Pembangunan Desa - Gunawan, Randi; Gultom, Muhammad Husin; Ajinar; Akhyari; Suhaeri; Syahrizal; Iskandar; Sabri (Yayasan Kawanad, 2022)
Law Number 6 June 2014 Village development plans must be carried out in a participatory manner, including the entire community, including sensitive groups (minorities, diverse, women, and the poor). The development carried out by the village is intended to be truly beneficial for all residents. So far, most villages in Indonesia have not been able to carry out legal missions. This is evidenced by the existence of a complete village without entangling the community with a transparent development plan. In addition, there are villages that try to involve the community through the “musrenbangdes” mechanism, but not all community components are invited to the “musrenbangdes”. As a result of non-participatory development planning, the benefits of village development are not felt by all levels of society, so the development program is not successful. The USK staff conducts training on village development planning, budgeting, and evaluation of village development results in Payakameng Village as an effort to realize a participatory village development plan. Representatives from all levels of the village community (village residents, administrators of social organizations, village government) participated in these activities. In this training, it is necessary to implement a participatory village development plan so that all residents can feel the results of development.